STUDY SELECTION OF FISHING PORT LOCATION IN TERKUL VILLAGE, IN RUPAT DISTRICT, BENGKALIS REGENCY OF RIAU PROVINCES - Manulang, Indah Ayu Lestari; Brown, Arthur; Zain, Jonny (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe experiment was conducted during of october 2014 in the village of Sei Injab (Sungai Injab) Village Terkul Rupat Bengkalis District of Riau Province. This study aims to determine the best location suitable for development to the fishing port from two candidates favored location.The method used is a survey method. By comparing its aspects such as physical aspects of technical, aspects of fisheries potential, demographic aspects and infrastructure aspects. The results of the analysis of the study data show that the port site selection based on a comparison of the two points of observation sites in Sei Injab (Sungai Injab), it can be concluded that the location A in RT.019 has many advantages in many aspects than location B in RT.023 for the construction of fishing ports.Key words: fishing fort, physical, fisheries potential, demographic, infrastructureaspects.